The billionaire raj : a journey through India's new gilded age - Crabtree, James (New York : TIM Duggan books, 2018)
"A colorful and revealing portrait of the rise of India's new billionaire class in a radically unequal society. India is the world's largest democracy, with more than one billion people and an economy expanding faster than China's. But the rewards of this growth have been far from evenly shared, and the country's top 1% now own nearly 60% of its wealth. In megacities like Mumbai, where half the population live in slums, the extraordinary riches of India's new dynasties echo the Vanderbilts and Rockefellers of yesterday, funneling profits from huge conglomerates into lifestyles of conspicuous consumption. James Crabtree's The Billionaire Raj takes readers on a personal journey to meet these reclusive billionaires, fugitive tycoons, and shadowy political power brokers. From the sky terrace of the world's most expensive home to impoverished villages and mass political rallies, Crabtree dramatizes the battle between crony capitalists and economic reformers, revealing a tense struggle between equality and privilege playing out against a combustible backdrop of aspiration, class, and caste. The Billionaire Raj is a vivid account of a divided society on the cusp of transformation--and a struggle that will shape not just India's future, but the world's"--Dust jacket flap
Part I: Robber barons. Ambaniland ; The good times begin ; Rise of the Bollygarchs -- Part II: Political machines. India modified ; The season of scams ; Money power politics ; Cronyism goes south -- Part III: A new gilded age. House of debt ; The anxious tycoons ; More than a game ; The nation wants to know ; The tragedies of Modi -- Conclusion: A progressive era?
Includes bibliographical references (pages 385-390) and index
Keywords: Billionaires -- India; Social classes -- India; India -- Economic conditions -- 1991-; India -- Social conditions -- 1947-